Perilaku Berisiko dalam Berkendara dan Kejadian Kecelakaan Sepeda Motor pada Mahasiswa - Amalia, Farah Multi; Nurmansyah, Mochamad Iqbal (Window of Health : Jurnal Kesehatan, 2020)
Traffic accidents are the leading cause of death in the young adult age group. This study aims to determine the relationship between risky behavior in driving and the incidence of motorbike accidents among students of UIN Syarif Hidayatullah Jakarta. This type of research is quantitative with cross sectional design. A sample of 502 students were selected using a purposive proportional sampling method. Data analysis was performed using the Chi-Square test. The results showed that 32.1% of respondents had a motorcycle accident. The statistical test showed that there was a relationship between listening to music while driving (p = 0.013), driving at a speed of more than 50km / h (p = 0.001), sudden braking (p = 0.000), and overtaking without giving a turn signal (p = 0.006) with motorcycle accident. Risky behavior can reduce a person's concentration in driving so that it can increase the chance of a motor vehicle accident. The university in particular needs to tighten regulations and education for students to be able to increase safe driving behavior.